Applying digital technologies to sustainable delivery of goods - Aurelija Burinskienė; Valentas Gružauskas; Gintarė Byčenkaitė (Entrepreneurship and Sustainability Issues)
This study explores how digital transformation drives sustainable practices in supply chains and related industries. The objectives focus on examining the integration of advanced digital technologies – to enhance environmental sustainability in logistics and production systems. Methodologically, the research analyses current literature and industry cases to identify key mechanisms and outcomes of digital initiatives. Key findings indicate that digital transformation significantly improves resource efficiency, reduces emissions, and minimises waste across supply chain operations. Digitalised supply chains improve transparency and optimise logistics, thereby cutting excess inventory and lowering the carbon footprint of transportation. In broader industry applications, Industry 4.0 technologies facilitate cleaner supply chain processes and real-time environmental monitoring. These advancements translate into tangible environmental benefits, including reduced energy consumption through smart automation and enhanced pollution control via data-driven decision-making. The study underscores that embracing digital transformation is pivotal for advancing sustainability goals. It enables firms and supply chains to achieve higher ESG performance, social responsibility, environmental and governance stewardship. However, it also highlights the need to address challenges, ensuring that digital innovations yield long-term environmental benefits without unintended drawbacks.